Awareness among dental practitioners about oil pulling - Its effect on the Corona Virus and immunocompromised patients: A questionnaire-based survey - Upasana Jayaram Reddy; Mithra N Hegde; Mallikarjuna Rao; Aditya Shetty; Jayarama Shetty; Nidhi Saha (Wolters Kluwer Medknow Publications, 2021)
Background: The ongoing pandemic has posed limitations to dental practice. In the current scenario of the coronavirus disease-2019 (COVID-19) pandemic, many patients present with symptoms like burning of the eyes, nose, throat, xerostomia, and mouth ulcers. For this, the Ministry of AYUSH is promoting oil pulling as a preventive measure. Aim: The aim of this study was to increase the awareness and confidence of dental practitioners in prescribing a simple technique for ameliorating common symptoms of COVID-19 infection - by oil pulling, in routine clinical practice. Methods: This study entailed designing a standardized web-based questionnaire for conducting a survey among dental practitioners from all specializations. Here, 100 participants answered 14 questions related to the role of oil pulling in treating oral symptoms common among COVID-19 patients and immunocompromised radiation patients. Statistical analysis was carried out after receiving all responses. Frequencies and percentages were calculated. Results: The results of the present survey indicated that 8.6% of total participants had good awareness (>16 Qs); 56.3% of total participants showed moderate awareness (10-16 Qs); while 35.2% had poor awareness (<10 Qs). Conclusion: Oil pulling can be deemed as an effective method of treating oral symptoms of COVID-19. Dentists should acquire adequate knowledge regarding the role and importance of this simple preventive measure.